An efficient architecture for the accurate detection and monitoring of an event through the sky - Sharma, Amit; Singh, Pradeep Kumar; Sharma, Ashutosh; Kumar, Rajiv (Computer communications, 2019)
The detection of an event at its early stage is still an open challenge and in its development stage. This manuscript is an attempt to identify the possibilities of Wireless Sensor Networks (WSNs) and Unmanned Aerial Vehicles (UAVs) in the applications of disaster management. Major of the applications of systems that utilizes both WSNs and UAVs are classified and architecture is proposed for detecting and monitoring the event at its early stage. The proposed system utilizes both sensor network and UAV network for the application of fire detection. The system is capable of sensing the environmental parameters in real time and possesses continuous monitoring until an event occurs. The main objective of this work is to develop such a system that serves accurate detection along with its confirmation through real time images from UAVs. The experimental simulation presents the accurate detection rate and the approach is adequate for early event detection. The improvements in early detection system significantly reduce the damage cause due to late detection of an event.